Detailed core and log analysis of a producing Viola dolomite well in Comanche County, Kansas - Hagood, William Kitchell, Jr. (Kansas State University, 2019)
The Ordovician-aged Viola Limestone of southwestern Kansas is a developing carbonate resource play with significant accumulations of hydrocarbons. The Viola surface is an unconformity, and production comes from regions of preserved dolomite on paleo-topographic highs. Evaluation of a cored interval of the upper Viola recognized several distinct facies, which were examined in conjunction with detailed well log analysis and X-Ray Fluorescence analysis to recognize facies control on Viola production. Five major facies were determined by petrographic analysis and core examination, labeled cherty dolomite, intraclastic breccia, intraclastic rudstone, bioclastic grainstone, and muddy dolostone. The depositional environments of the facies were interpreted to be a shallow marine environment, ranging from low to high energy, with the cherty dolomite and muddy dolostone facies being classified as low energy, and intraclastic breccia, intraclastic rudstone, and bioclastic grainstone facies classified as high energy. The Viola formation has been divided into zones, based on well log signatures and are named the “A”, “B”, and “C” zones. The cherty dolomite is the only observed reservoir quality facies in the core, due to the “A” zone not being recovered from coring and comprises the majority of the “B” zone. The cherty dolomite has density porosity (DPHI) values up to 34% and only appears once in the cored section, with a thickness of roughly 8ft (2.4m). The “A” and “B” zones are the chief producers of the Viola Limestone in south-central Kansas. In the core of the study well, from Rich C #7 of the Herd field in Comanche County, Kansas, the “B” zone is capped by alternating thin beds of rudstone and breccia petrofacies, along with a thin layer of breccia near the bottom of the “B” zone. Muddy dolostone with thin layers of rudstone mainly comprise the area between the “B” and “C” zone and below the “C” zone. The “C” zone well log facies is non-productive, and consists mainly of muddy dolostone, with a thin layer of rudstone marking the top of the zone in the Rich C #7 core. An almost two-foot-thick layer of rudstone is located a couple feet below the top of the “C” zone. Wire-line log signatures differentiated the “A”, “B”, and “C” zones and cherty dolomite facies in Rich C #7 and correlate easily with other Viola-producing wells in south-central Kansas, like Herd 1. The productive well log facies can be identified from neutron porosity (NPHI), DPHI, and sonic log (DT) signatures and are discriminated by cross plots of NPHI, DPHI, and DT. The chemical data from the handheld XRF machine was able to partly discriminate well log facies and some described facies using specific elemental signatures and ratios. All of the well log facies and the cherty dolomite, rudstone, and muddy dolostone petrofacies were discriminated from plotting Si versus Al, Si/Al versus Ti, Si/Al versus Zr. The Zr vs Ti cross plot was only able to discriminate the “B” zone and cherty dolomite petrofacies. P-Wave velocity measurements exhibited correlations to the NPHI, DPHI, and sonic log values of Rich C #7. The “B” zone correlates exactly with the P-Wave velocities, with the cherty dolomite facies being discriminated by the velocities. This study illustrates the advantages of correlating depositional facies with reservoir quality and linking specific reservoir petrofacies with well log signatures, ultimately to create a greater understanding of the controls on reservoir quality to aid in predicting new areas of exploration.
Keywords: Carbonate Geology; Petroleum Geology; Viola Limestone; Sedimentary Geology; Depositional Environment; Geology